Ruth Gordon and Garson Kanin papers - Bagnold, Enid.; Bagnold, Enid.; Gordon, Ruth, 1896-1985.; Kanin, Garson, 1912-1999.; Columbia Pictures Corporation; Columbia Pictures Corporation; Metro-Goldwyn-Mayer.
Correspondence, attached newspaper clippings and printed ephemera, and miscellaneous personal files. Correspondence relates to the American theater and film industry; symbolism and characterizations in A Matter of Gravity: A Comedy in Three Acts and The Chalk Garden; Gordon's collection of haute couture designed for her by Mainbocher (Main R. Bocher); film personalities including Judy Holliday and Spencer Tracy; production of films such as It Should Happen to You, The Actress, and The Marrying Kind; and London theater during World War II. Correspondents include Enid Bagnold, Cecil Beaton, Hugh Beaumont, Maurice Chevalier, Harry Cohn, George Cukor, Dame Edith Evans, Sir Tyrone Guthrie, Mainbocher, Laurence Olivier, and Dore Schary.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Ruth Gordon, author and actress, and her husband, Garson Kanin, actor, author, director, and producer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bagnold, Enid -- Correspondence; Beaton, Cecil, -- 1904-1980 -- Correspondence; Beaumont, Hugh, -- 1909-1982 -- Correspondence; Chevalier, Maurice, -- 1888-1972 -- Correspondence; Cohn, Harry, -- 1891-1958 -- Correspondence; Cukor, George, -- 1899-1983 -- Correspondence; Evans, Edith, -- Dame, -- 1888-1976 -- Correspondence; Guthrie, Tyrone, -- Sir, -- 1900-1971 -- Correspondence; Holliday, Judy; Mainbocher, -- 1891-1976 -- Correspondence; Olivier, Laurence, -- 1907-1989 -- Correspondence; Schary, Dore -- Correspondence; Tracy, Spencer, -- 1900-1967.; Fashion -- United States; Motion picture actors and actresses; Motion picture industry -- United States; Symbolism; Theater -- England -- London; Theater -- United States; World War, 1939-1945 -- Theater and the war; Actors; Authors; Motion picture directors; Motion picture producers; Theatrical directors; Theatrical producers